(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
In this interview, Nan Travers and Alan Mandell engage Professor Per Andersson of Linköping University in a reflective conversation on recognition of prior learning (RPL) and its implications for migrants, refugees, and displaced learners. Andersson challenges conventional reliance on formal qualifications by inviting readers to reconsider how competence is defined, assessed, and valued. The dialogue gestures toward a shift from labor-market-driven approaches to perspectives grounded in individuals’ lived experience and learning. It also raises questions about assessment, validity, and inclusion without resolving them, pointing instead to productive tensions within RPL practice.